(untitled) (Journal of Applied Oral Science, 2010)
OBJECTIVE: This study aimed to evaluate the bending moments, and compressive and tensile forces in implant-supported prostheses with three, four or five abutments. MATERIAL AND METHODS: Ten Pd-Ag frameworks were tested over two master models with: 1) parallel vertical implants, and 2) tilted distal implants. Strain gauges were fixed on the abutments of each master model to measure the deformation when a static load of 50 N was applied on the cantilever (15 mm). The deformation values were measured when the metallic frameworks were tested over three, four or five abutments, and transformed into force and bending moment values. Data were analyzed by ANOVA and Tukey's test for multiple comparisons at 5% level of significance. RESULTS: Abutment #1 (adjacent to the cantilever) had the highest values of force and sagittal bending moment for all tests with three, four or five abutments. Independently from the number of abutments, axial force in abutment #1 was higher in the vertical model than in the tilted model. Total moment was higher with three abutments than with four or five abutments. Independently from the inclination of implants, the mean force with four or five abutments was lower than that with three abutments. CONCLUSION: The results suggest that in the set-ups with four or five abutments tilted distal implants reduced axial force and did not increase bending moments.